Role of defects and grain boundaries in the thermal response of wafer-scale hBN films. (24th November 2020) - Bera, K; Roy, Anushree; Chugh, D; Wong-Leung, J; Hoe Tan, H; Jagadish, C
Abstract: With more widespread applications of nanotechnology, heat dissipation in nanoscale devices is becoming a critical issue. We study the thermal response of wafer-scale hexagonal boron nitride (hBN) layers, which find potential applications as ideal substrates in two dimensional devices. Sapphire-supported thin hBN films, 2′′ in size and of different thicknesses, were grown using metalorganic vapour phase epitaxy. These large-scale films exhibit wrinkles defects and grain boundaries over their entire area. The shift of E 2 g high phonon mode with temperature is analysed by considering the cumulative contribution of anharmonic phonon decay along with lattice thermal expansion, defect, and strain modulation. The study demonstrates that during heat treatment the strain evolution plays a dominating role in governing the characteristics of the wrinkled thinner films. Interestingly we find that both defects and strain determine the spectral line-width of these wafer-scale films. To the end, from Raman line-width, the changes in phonon lifetime in delaminated and as-grown films is estimated. The results suggest the possibility of a reduction in thermal transport in these wafer-scale films compared to their bulk counterpart.